2022
DOI: 10.3390/cells11040656
|View full text |Cite
|
Sign up to set email alerts
|

C-C Chemokine Receptor 7 in Cancer

Abstract: C-C chemokine receptor 7 (CCR7) was one of the first two chemokine receptors that were found to be upregulated in breast cancers. Chemokine receptors promote chemotaxis of cells and tissue organization. Since under homeostatic conditions, CCR7 promotes migration of immune cells to lymph nodes, questions immediately arose regarding the ability of CCR7 to direct migration of cancer cells to lymph nodes. The literature since 2000 was examined to determine to what extent the expression of CCR7 in malignant tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 298 publications
(466 reference statements)
1
11
0
Order By: Relevance
“…The malfunction of the immune receptor and immune recognition receptor activity will also lead to immune escape and worsen the condition and so does the mutation of C-C chemokine. There has been evidence indicating that the expression of C-C chemokine receptor 7 in malignant tumors promoted migration to the lymph nodes ( 39 ), which will make the prognosis worse. And for the GO term “cytokine binding”, because some cytokines bind to particular G-protein-coupled seven-span transmembrane receptors, which are important regulators of cell trafficking and adhesion, abnormal cytokine binding/receptor activity, cytokines’ malfunction may promote the spread of cancer cells and worsen prognosis ( 40 ) thus leading to a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The malfunction of the immune receptor and immune recognition receptor activity will also lead to immune escape and worsen the condition and so does the mutation of C-C chemokine. There has been evidence indicating that the expression of C-C chemokine receptor 7 in malignant tumors promoted migration to the lymph nodes ( 39 ), which will make the prognosis worse. And for the GO term “cytokine binding”, because some cytokines bind to particular G-protein-coupled seven-span transmembrane receptors, which are important regulators of cell trafficking and adhesion, abnormal cytokine binding/receptor activity, cytokines’ malfunction may promote the spread of cancer cells and worsen prognosis ( 40 ) thus leading to a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…LAG3 can promote glioma progression by regulating the proliferation, migration, and invasion of glioma cells ( He et al, 2015 ), and inhibition of LAG3 suppresses the invasion of ovarian cancer ( Wang et al, 2015 ). Bill et al (2022) suggested that CCR7 plays distinct roles in directing tumor cells to the lymph nodes, skin, and central nervous system. Zhu et al (2018) demonstrated that downregulated VSIG4 expression was related to poor prognosis in hepatocellular carcinoma patients with hepatitis B infection.…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by CCR7 belongs to the G protein coupled receptor family, which activates B and T cells and is found in many lymphoid tissues. It has been demonstrated that it can inhibit memory T cell migration to inflammatory tissue while also promoting dendritic cell maturation ( Bill et al, 2022 ). In lymph nodes, the signal mediated by this receptor regulates the homeostasis of T cells and might possibly be involved in T cell activation and polarization, as well as the pathogenesis of chronic inflammation ( Bill et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that it can inhibit memory T cell migration to inflammatory tissue while also promoting dendritic cell maturation ( Bill et al, 2022 ). In lymph nodes, the signal mediated by this receptor regulates the homeostasis of T cells and might possibly be involved in T cell activation and polarization, as well as the pathogenesis of chronic inflammation ( Bill et al, 2022 ). Flores-Mejía et al ( Flores-Mejía et al, 2019 ) examined blood samples from sepsis patients and healthy volunteers and found that CCR7 was overexpressed in NK cells.…”
Section: Discussionmentioning
confidence: 99%